Spolno občutljiva raba jezika v učnih gradivih - Kranjc, Simona (Slavistična revija, 2019)
In this article, I focus on some questions of language and gender that are set in elementary school teaching materials. I discuss issues of addressing female and male pupils in instructions and using generic male sex and gender stereotypes in examples and sexually stereotypical contents in both verbal and non-verbal discourse.
Keywords: elementary school; gender roles; gender sensitive use of language; generic male gender; generičnost moškega spola; osnovna šola; spolne vloge; spolno občutljiva raba jezika; stereotipi; stereotypes; teaching materials; učno gradivo